INDEPENDENSI HAKIM AD-HOC PADA LINGKUNGAN PERADILAN HUBUNGAN INDUSTRIAL - Muhammad Ishar Helmi; Riko Hendra Pilo (Jurnal Hukum dan Peradilan, 2017)
PPHI (Industrial Relations Disputes Settlement) Act regulates the principle of settlement of industrial relations disputes by consensus, if there is a dispute between employee/workers and employers, the first stage of dispute settlement shall be submitted to disputing party (bipartite settlement). The provisions of Article 63 paragraph (2) and Article 67 paragraph (1) sub-paragraph f of the Act shall result in the ad-hoc judges of the Industrial Relations Court, in carrying out their duties and responsibilities to examine and decide a case shall be independent and kept away from any intervention of any institution. The ad-hoc judges of the Industrial Relations Court is a judge proposed by a trade union, employers organization, also dismissed respectfully by the trade union and the employers organization. This will undermine the free, impartial and clean judicial system that dreams of because the judges will be ruled by the litigants, as the judge is appointed and dismissed by the party to be tried in the industrial relations court.Keywords: judicial independence, ad-hoc judges, PHI